IMPROVING HUMAN RESOURCES FOR FIELD OFFICERS IN ANIMAL HEALTH HANDLING SERVICES AND ARTIFICIAL INSEMINATION IN PULANG PISAU REGENCY, CENTRAL KALIMANTAN - Sunaryo Hadi Warsito; Herry Agoes Hermadi; Nanik Hidayatik; Mirni Lamid (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
The community service at Universitas Airlangga in Pulang Pisau Regency, Central Kalimantan aims to increase the capacity of field officers of Pulang Pisau's Agricultural Service regarding artificial insemination and livestock health management. The method used in achieving these goals is through socialization and training on artificial insemination and handling livestock health. These activities include: counseling and training on artificial insemination techniques and the handling of reproductive disorders and disease management in beef cattle. The results of the community service evaluation show that in general the knowledge of the community service participants has increased compared to before this activity was carried out. This can be seen from the results of the questionnaires that have been filled out by the participants. The number of participants who knew about the types of livestock reproductive disorders and good AI techniques increased from 66.7% to 90.5%. Likewise, the knowledge of participants about the types of animal health disorders and how to properly handle them before the activity was 71.4% and after the activity increased to 95.2%. Key words: field officers, animal health, artificial insemination, Pulang Pisau Regency DAFTAR PUSTAKA Arianti, N., Inggriati, N.W.T., Sarini N.P. (2020). Hubungan antara Karakteristik Inseminator dengan Keberhasilan Inseminasi Buatan pada Ternak Sapi di Kabupaten Tabanan. Peternakan Tropika, 8: 1-15. Arisandi, R. (2017). Evaluasi Keberhasilan Inseminasi Buatan di Kecamatan Tombolopao Kabupaten Gowa. [Skripsi]. Universitas Islam Negeri Alauddin Makassar. Dharmayudha, A.A.G.O., Anthara, M.S., Sukada, I.M., Ardana, I.B.K. (2019). Pelayanan Kesehatan dan Pemberantasan Penyakit Ternak Sapi Bali dalam Mendukung Program Swasembada Daging Sapi di Desa Buruan Blahbatuh Gianyar. Buletin Udayana Mengabdi, 18: 95-98. Badan Pusat Statistik Dinas Pertanian dan Peternakan Provinsi Kalimantan Tengah. (2018). https://kalteng.bps.go.id/ [diakses pada 24 Februari 2021]. Herawati, T., Anggraeni, A., Praharani, L., Utami, D., Argiris, A. (2012). Peran Inseminator dalam Keberhasilan Inseminasi Buatan pada Sapi Perah. Informatika Pertanian, 21: 81-88. Labetubun, J., Parera, F., Saiya, S. (2014). Evaluasi Pelaksanaan Inseminasi Buatan pada Sapi Bali di Kabupaten Halmahera Utara. Agrinimal Vol. 4 No. 1 : 22-27.